Seronegative Adult Autoimmune Enteropathy in a Male Traveler. Issue 1 (2017) - McCabe, Patrick; Alli‐Akintade, Latifat; Stondell, Jesse
ABSTRACT : N/A: Autoimmune enteropathy (AIE) is rare but damaging. The lack of consistent objective findings makes diagnosis a challenge. A 45‐year‐old male developed noninfectious diarrhea with significant weight loss and electrolyte abnormalities. Computed tomography delineated enteritis. Colonoscopy and esophagogastroduodenoscopy showed villous atrophy, chronic inflammation, and ulceration of the terminal ileum and cecum. Pathology showed cryptitis with apoptosis and abscesses throughout the small and large bowel and absent goblet cells. Steroids rapidly improved symptoms. Anti‐enterocyte antibody serologies were negative. Management can be challenging, and, in this case, the patient initially improved with budesonide and infliximab but required alternative antitumor necrosis factor therapy after relapsing. This is an unusual presentation of seronegative AIE, which should be considered in cases of persistent severe diarrhea.